Pengaruh Pengetahuan Pajak, Self Assessment Sytem, Pelayanan Fiskus dan e-Filing terhadap Kepatuhan Wajib Pajak - Arsita Fajria Hidayati; Kartika Hendra Titisari; Sari Kurniati (Ekonomis: Journal of Economics and Business, 2022)
The purpose of this study was to examine and analyze the effect of tax knowledge, self-assessment system, Fiscal Service, and e-Filing on taxpayer compliance. This type of research is descriptive quantitative. The population in this study is 4,975 Micro, Small and Medium Enterprises that are active and registered during 2021 at KPP Pratama Klaten. The research sample was 100 respondents, with simple random sampling method. This study uses a questionnaire in data collection. The data analysis technique used multiple linear regression. The results showed that tax knowledge, self-assessment system and tax service services had a positive and significant effect on taxpayer compliance, while e- Filing had no effect on taxpayer compliance.